What is the best way to collect maximum forward lumbar spine flexion values for normalizing posture to range of motion?. (16th April 2020) - Frey, Mona; Greene, Ryan; De Carvalho, Diana
Abstract: Spine angles are an important measure in biomechanics research and are commonly normalized to a percentage of range of motion. However, standardized methods to collect the reference posture trials for this normalization do not exist. The purpose of this study was to determine posture (seated or standing) and number of trials that should be collected and how to calculate the angle that best represents the maximum range. Forty healthy adults (22 females, 18 males) completed 12 reference trials: 1 upright standing, 5 standing flexion, and 5 seated flexion trials. The maximum lumbar angle was found for each flexion trial. Additionally, different methods to calculate the maximum were applied by taking the maximum of the 5 standing, 5 seated, and all 10 flexion trials. An interaction was found between posture, order, and trial number. 42.5% and 57.5% of participants reached their maximum angle during seated and standing flexion respectively which may be due to back- vs hip-dominant movement strategies. 85% of participants achieved their maximum at some point during the first six flexion trials. The maximum angle of all 10 flexion trials was significantly greater than the angle of the first standing or seated trial only but not significantly greater than the maximum of all seated or standing flexion trials respectively. Secondarily, no differences in the maximum lumbar angle were found between sexes. This study suggests that 6 flexion trials, involving both standing and seated flexion, should be collected to best represent the maximum end range of spine flexion.